Colon cancer microsatellite instability influences computed tomography assessment of regional lymph node morphology and diagnostic performance. Issue 154 (September 2022) - Kim, Yong Tae; Min, Ji Hye; Choi, Kyue-Hee; Kim, Honsoul
Highlights: CT showed that microsatellite instability state affects the regional lymph node size. In MSI-high tumors, small lymph nodes were associated with a lower risk of metastasis. CT of only MSI-high tumors predicted node negative patients with high specificity. Abstract: Purpose: To elucidate whether a high level of microsatellite instability (MSI-high) in colon cancer influences the CT assessment of regional lymph node (rLN) morphology and diagnostic performance on predicting pathological node-negative (pN0) patients. Method: We retrospectively reviewed 507 patients with cecal/proximal ascending colon cancer (age, 63.0 ± 11.6 years; MSI-stable, n = 398; MSI-high, n = 109) who underwent right hemicolectomy between July 1, 2009, and December 31, 2018. Preoperative CT images were assessed for number of rLNs, long/short diameter of the largest rLN, and CT LN grade (CTN0, low probability of metastasis; CTN1, borderline; CTN2, high probability). Sensitivity, specificity, positive predictive value and negative predictive value for predicting pN0 was calculated. Multivariable logistic regression analysis was performed. Statistical significance was defined as P < 0.05. Results: A study population of 507 patients (mean age ± standard deviation, 63.0 ± 11.6; 264 women) were evaluated. In patients with rLN metastasis, the rLN long axis (pN1: P = 0.013, pN2: P = 0.039) and short axis (pN1: P = 0.001, pN2: P = 0.009) were both longer in MSI-high tumors compared with MSI-stable tumors. High specificity for predicting pN0 was only achieved in MSI-high tumors [sensitivityMSI-stable  = 58.3% (n = 137/235), specificityMSI-stable  = 71.2% (n = 116/163); sensitivityMSI-high  = 38.4% (n = 33/86), specificityMSI-high  = 91.3% (n = 21/23)]. Multivariable logistic regression indicated MSI-high (P < 0.001, odds ratio = 3.701), smaller LN long axis (P = 0.023, odds ratio = 0.905), and lower CT LN grade (CTN0: P = 0.009, odds ratio = 2.987; CTN1: P = 0.014, odds ratio = 2.195) as significant parameters in predicting pN0. Conclusion: MSI-high colon cancer is associated with larger rLNs and high specificity for predicting pN0 on CT assessment.